The mergers and splits that occurred with Ahdut Ha'avoda (1930- 1968 AD) - Abu Halabia, Hasan Abdalla (Journal of Humanities & Social Sciences, 2021)
The Ahdut Ha'avodah party is one of the most important Arab Zionism that emerged during the twenties of the twentieth century, due to its essential role in the formation of the Zionist institutions that contributed to the establishment of the (Jewish state). AD, and its formation, the Mapai Party, until its formation in the Israeli Labor Party in 1968 with the Mapai and Rafi parties, in addition to the most prominent ideas of the party in every stage in it, in addition to the reasons that lead to those initiatives that were established in those events, and highlighting the most important party, the party in every stage. Stage of its stages, The study aimed to know the mergers and splits that occurred with the Ahdut Ha'avoda party since its union in 1930AD, and its formation of the Mapai Party, until its formation in the Israeli Labor Party in 1968 with the parties of Mapai and Rafi, in addition to identifying the most prominent ideas and programs of the party at each stage in which it is located, in addition to knowing The reasons that led to those mergers and splits that occurred with the party, and to highlight the most important leaders of the party in every stage of its stages, and the researcher followed in his study on the methodology of historical and descriptive analytical research, by narrating the historical events and then expressing an opinion about them, among the most important results he reached The researcher in his research is as follows:1.Ahdut Ha'afudah played an important role in uniting the Zionist workers in Palestine, through the formation of the Mapai Party.2.One of the main reasons for the emergence of Bloc B and the leftist movement in the Mapai party was its objection to the foreign policy of the party, and its demand for the restoration of democracy to its institutions, and it split from the Mapai party in May 1944, and established a new party that took for itself the historical name of the Ahdut movement Ha'avoda: “Give it to Lahoud Ha'foda” (The Movement for Labor Union).3.Ahdut Ha'avoda saw himself as the sole heir of the historical Ahdut Ha'avoda movement, carrying the general idea of ​​unification of the Zionist socialist parties in the land of (Israel).4.The Ahdut Ha'avodah Party derives its main strength from the kibbutz movement, which is called the (Hakibbutz Ha'avodah Movement - United Kibbutz).5.Contacts took place between the Ahdut Ha'avoda and Bay parties during the years 1964- 1965AD to form an electoral alliance between them, and the supporters of Achdut Ha'Afoudah supported that approach. Because of the ideological attrition among party members.6.On May 19, 1965 AD, the alliance agreement between the Mapai parties and Ahdut Ha'avodah was signed in Haifa, despite the opposition of the minority in the two parties, whether the minority in the Mapai party led by David Ben- Gurion, or the minority led by (Yitzhak Tabenkin) - the spiritual leader of the party Ahdut Haafodah -.7.The two- party alliance agreement stipulated that the two allied parties present a joint list of candidates in the Knesset and Histadrut elections, municipalities, the world Zionist movement, and other bodies in which the elections are held on a party basis under the name (The Alliance for the Unity of Israel Workers) - HaArakhtan (The Small Gathering).8.The 1967 AD war highlighted the idea of ​​unifying the four workers' parties in (Israel): Mapai, Ahdut Ha'avodah, Rafi and Mapam.Based on the findings, the study recommends the following:1- That the Palestinian and Arab research centers pay attention to Zionist affairs.2- Draw lessons from the history of Zionist workers' parties and their role in establishing the Zionist state; (Israel), and the possibilities of benefiting from that experience in the Palestinian reality through:o Benefiting from the party experience (the Zionist workers parties) of the Palestinian parties.o Planning and preparation is an element of success in party work.o Competition between parties for the common good.3- That some researchers in modern history proceed to prepare studies in the history of Zionism, by referring to the Hebrew sources and references.4- Research centers' interest in translating Hebrew sources and references, to assist researchers in the history of the Zionist movement.
Keywords: Ahdut HaAvodah; Labor Party; Zionism; Israel; Zionist parties; Rafi; Labor; Mapai